Distant higher education under self-isolation and the problem of institutional traps - V. V. Volchik; I. M. Shiriaev (Russian Journal of Economics and Law)
Objective: to reveal the consequences of the transition to total distance education in the Russian higher education under self-isolation caused by the spread of the new coronavirus.Methods: qualitative methods, narrative analysis, in-depth interviews, included observation.Results: the process of transition to distance education with a view to combat the spread of the new coronavirus infection in Russia in 2020 is a unique example of simultaneous implementation of institutional and technological innovations. The analysis of this phenomenon requires using the ideas of institutional and evolutionary economic theory, as well as narrative economics and the Austrian school.To determine the main patterns of emergence and strengthening of institutional traps that arise under self-isolation in the higher education system, the authors analyzed the narratives and in-depth interviews of the main actors. In addition, a certain part of the conclusions is formulated based on the included observation of the authors as typical representatives of the higher education sphere. The conducted research allowed identifying the main patterns of the current total introduction of distance technologies in the Russian higher education. It is stated that institutional and technological evolution can lead to the selection and consolidation of inefficient institutions and technologies under the influence of increasing returns. The widespread introduction of distance education demonstrates its defects. Based on the analysis of the results of in-depth interviews, conclusions about the main institutional problems of the educational process digitalization are formulated. Distance education is not a full-fledged substitute for the traditional education, as it impedes the transfer of implicit knowledge, controland feedback during training, ambiguously influences the costs of educational activities, and does not allow relying on the reliability of information and communication technologies. Transition to distant education can be interpreted as a new stage of evoluton of the institutional trap of electronization and digitalization..Scientific novelty: consists in identifying the qualitative characteristics of the process of implementing total distance education while combating the spread of the new coronavirus infection in Russia.Practical significance: is determined by the need to understand the causes of inefficiency and aggravation of contradictions between different groups of actors in the field of education and science while combating the spread of the new coronavirus infection.